Dansyl- and rhodamine-based fluorescent sensors for detecting singlet oxygen and superoxide production in plants in vivo - Barta, Csengele (Acta Biologica Szegediensis, 2002)
Reactive oxygen species (ROS) play a key role in a variety of biotic and abiotic stress conditions, therefore their direct measurement in vivo is of special importance. In this study, we describe two dansyl-based ROS sensors, the singlet oxygen specific DanePy; HO-1889NH, which is reactive to both singlet oxygen and superoxide radicals and a rhodaminebased singlet oxygen sensor, HO-2941. In order to characterise the potential use of these chemosensors in plant experiments in vivo, we characterise their ROS trapping ability, fluorescence emission spectra and localisation in spinach leaves.